KAJIAN OPERASIONAL SISTEM POLDER UNTUK PENANGANAN BANJIR DAN ROB DI KAWASAN GENUK SEMARANG - Adi, Henny Pratiwi; Wahyudi, Imam (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2021)
The Kaligawe Genuk area is the main route for the North Coast (Pantura) of Java.The area is the gateway to the city of Semarang from the east direction. Since 2005,this area has frequently had floods caused by tides (tidal floods) and rainfall. TheCentral Government, supported by the Semarang City Government, built the KaliTenggang and Sringin Polder systems from 2016 to 2019. In terms of capacity, thissystem is not yet perfect for dealing with floods, and it requires efforts so that thesystem can be operated optimally. This study activity aims to simulate rainfall flowrate, the pump capacity, and the retention pond. The simulation results will becomethe basis for the development of the polder system operational manual. Theimplementation method collects secondary rainfall data, reviewing the condition ofa catchment area, retention pond, and pump station. Focus group discussion withstakeholders done in the Kaligawe Genuk area. The location of the activity is morefocused on the Kali Sringin area. This study produces tables and graphs of pumpcapacity simulation, retention ponds, and an operational manual for the SringinPolder system. It is hoped that this guideline will become the basis for the poldersystem's sustainable operations.